Analisis Pengaruh Pengembangan Sumber Daya Manusia Terhadap Efektivitas Organisasi di Sektor Asuransi: Studi Kasus di PT ABC Insurance - Nina Rohmadhani; Mohamad Wafdy; Ashar; Sitti Rakhman (Premium Insurance Business Journal, 2024)
This research discusses work environment management, human resource acquisition and development, and compensation systems that support economic, social and environmental sustainability at PT ABC Insurance. Inclusive and adaptive work environment management can improve company performance by creating a harmonious work atmosphere and minimizing work stress. This research shows that implementing sustainable HRM that integrates sustainability aspects in work environment management, HR acquisition, career development, and compensation can create a positive impact on overall company performance and increase competitiveness in a competitive market.